A Comparative Analysis of Buddhist Asceticism and Islamic Zuhud: Philosophical Foundations and Contemporary Relevance - Fajar Amin, Muhammad; Untung, Syamsul Hadi (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background; Modern society is increasingly characterized by materialism and consumerism, which often lead to a spiritual crisis and a loss of meaning in life. In response, Buddhist asceticism and Islamic zuhud are often proposed as ethical alternatives. However, both are frequently misunderstood as purely anti-worldly or escapist doctrines. Objectives: This study aims to analyze and compare the conceptual and philosophical foundations, as well as the ethical and social implications, of asceticism in Buddhism and zuhud in Islam. Method: It employs a qualitative library research method with a comparative-analytical approach, examining primary scriptures and relevant academic literature.Result: The findings show that although both traditions emphasize self-control, they differ in their ontological foundations. Buddhist asceticism represents a non-theistic path toward liberation from suffering (dukkha). In contrast, Islamic zuhud is a theocentric practice that prioritizes the hereafter without neglecting worldly responsibilities.In practice, Buddhist asceticism tends to be institutionalized within monastic life, whereas zuhud functions as a flexible inner attitude applicable across social roles.Conclusion: This study concludes that both concepts offer a corrective framework against modern materialism and provide spiritual pathways toward a balanced and meaningful life.Implication: These findings contribute to interfaith dialogue and deepen the understanding of comparative spirituality.